Sistem Pengendali Suhu dan Kelembaban Udara Prototipe Greenhouse pada Tanaman Hidroponik menggunakan Metode Regresi Linier Berganda berbasis Arduino - Julisya Thana Khriswanti; Hurriyatul Fitriyah; Barlian Henryranu Prasetio (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Greenhouses can protect plants from erratic weather and plant pests. One of the optimal planting methods to grow in a greenhouse is wick hydroponics. Hydroponic wick is static because it relies on the principle of capillarity which causes high temperatures and poor dissolved oxygen due to the transfer of oxygen from the solution to the air. However, not necessarily hydroponic wick plants are perfectly protected in a greenhouse. The greenhouse effect is an event where some of the heat that penetrates into the greenhouse is then trapped inside so that the greenhouse air temperature becomes warmer. Warm temperatures affect plant growth because the temperature rises and humidity drops. To create optimal temperature and humidity, this research aims to create a temperature and humidity control system. Multiple linear regression is used to control the system, so that the system can run and adjust according to the time predicted by the multiple linear regression model. The temperature and humidity sensor used is a DHT22 sensor with an error during detecting temperature of 5.47% and humidity of 4.85%. In the system, the mean time of multiple linear regression computation is 111 milliseconds. The multiple linear regression model that used to control the system is very good with an error of 7.34%. The system works well and can lower the temperature and increase the humidity.